The emergence and future of central counterparties - Thorsten V. Koeppl; Cyril Monnet (Queen's University, Department of Economics, 2010)
We explain why central counterparties (CCPs) emerged historically. With standardized contracts, it is optimal to insure counterparty risk by clearing those contracts through a CCP that uses novation and mutualization. As netting is not essential for these services, it does not explain why CCPs exist. In over-the-counter markets, as contracts are customized and not fungible, a CCP cannot fully guarantee contract performance. Still, a CCP can help: As bargaining leads to an inefficient allocation of default risk relative to the gains from customization, a transfer scheme is needed. A CCP can implement it by offering partial insurance for customized contracts.
Keywords: G2; G13; D53; D82; 330; Counterparty Risk; Novation; Mutualization; Over-the-counter Markets; Customized Financial Contracts; OTC-Handel; Verrechnungsverkehr; Allokationseffizienz; Entscheidung bei Risiko; Theorie